THE UKM KAGAMA’S ROLE OF STAIN MANDAILING NATAL IN STRENGTHENING RELIGIOUS MODERATION FOR STUDENTS AT MUSTHAFAWIYAH PURBA BARU - Gamasari, Rita; Kurniawan, Servant (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
In the midst of the government's incessant program to strengthen religious moderation through Islamic boarding schools, Musthafawiyah as one of the oldest and largest salafi Islamic boarding schools in Sumatra has its own potential and challenges in strengthening religious moderation. STAIN Mandailing Natal as the closest tertiary institution to the Mustafawiyah Islamic boarding school through the Kagama UKM has taken part in carrying out its role in strengthening religious moderation in the Mustafawiyah santri environment. This study aims to explain the role of UKM Kagama in strengthening religious moderation in the Musthafawiyah santri environment. This research is descriptive with a qualitative approach. Data collection techniques are through observation, interviews, documentation, descriptive analysis, and drawing conclusions. The results showed that Kagama STAIN Mandailing Natal UKM played a very important role in strengthening religious moderation in the Musthafawiyah students. The role of UKM is realized through training and coaching in the five fields that are being studied by Kagama UKM, namely the yellow book, syarhil qur'an, tahfiz, recitations and rose accounting. In order to strengthen religious moderation, Kagama UKM members directly interact and discuss with students in the Islamic boarding school environment, both reviewing contemporary interpretation books, reviewing religious moderation texts for syarhil qur'an, guiding recitations and tahfiz readings, and practicing rose accounting skills. The actualization of the role of UKM Kagama is expected to be able to equip students spiritually and religiously so as to form individual students who are religious, have a nationalist spirit and accept diversity and are trained to be tolerant but still consistent, because these attitudes will form a moderate spirit in presenting Islam that is rahmatan lil natural.